Accuracy of the Indonesian child development pre-screening questionnaire - Syahperlan Wendi Simangunsong; Soeroyo Machfudz; Mei Neni Sitaresmi (Indonesian Pediatric Society, 2012)
Background Early stimulation, detection and intervention areimportant for child development and are recommended in theearly years of childhood for optimal results. The Indonesianchild development pre-screening questionnaire, Kuesioner PraSkrining Perkembangan (KPSP), has been widely used in publichealth centers (PHC) and community health centers (CHC)in the country. Howevei; the accuracy of this test has not beenadequately assessed.Objective To assess the diagnostic value of KPSP as a prescreeningtool for child development compared to that of theDenver II developmental screening test.Methods We conducted a KPSP diagnostic study, using theDenver II test as a gold standard for comparison. Subjects werechildren aged 3 to 60 months. They were recruited from one ofthree settings: hospital, community (child care centers) or schools(kindergarten).Results Of 210 children recruited, 182 were included in ourstudy. The overall sensitivity, specificity, positive predictive value(PPV), negative predictive value (NPV) and accuracy of KPSPwere 68.8%, 86.6%, 64.7%, 88.6% and 81.9%, respectively. Thecomparison of diagnostic value based on age groups showed betterresults in the 3 - 24 month group than that of the older group.Sensitivity, specificity and accuracy of the younger group vs. theolder group were 92.3% vs. 60.0%, 78.6% vs. 87.5% and 85.2%vs. 81.3%, respectively.Conclusion The accuracy of KPSP compared to Denver II testwas good for the 3 - 24 month age group. However, this toolshould be revised for the older age group. [Paediatr lndones.2012;52:6-9].